2010
DOI: 10.1007/s00467-009-1422-4
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptors 2 and 4 in renal ischemia/reperfusion injury

Abstract: Toll-like receptors (TLRs) are an evolutionarily conserved family of cell membrane receptors that are part of the innate immunity system playing an important role as a first response to tissue injury. TLR2 and TLR4 are constitutively expressed on renal epithelium, and their expression is enhanced following renal ischemia/reperfusion (I/R) injury. Genetic deletion of either TLR2 or TLR4 protects from renal I/R injury. However, it is not known whether deletion of both combined protects the kidney more than a del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 13 publications
3
56
2
Order By: Relevance
“…One of the crucial works linking innate immunity and acute kidney injury could show that TLR2-deficient mice are protected from renal ischemia/reperfusion injury (I/R) (Leemans et al 2005). This finding was confirmed for TLR 4 and double-deficient mice for TLR 2/4 in the same model (Rusai et al 2010). Moreover, the blocking of IL-1 RA was able to ameliorate kidney injury in a rat model of I/R (Rusai et al 2008).…”
Section: The Role Of Inflammation and Fibrosis In Chronic Kidney Diseasesupporting
confidence: 54%
“…One of the crucial works linking innate immunity and acute kidney injury could show that TLR2-deficient mice are protected from renal ischemia/reperfusion injury (I/R) (Leemans et al 2005). This finding was confirmed for TLR 4 and double-deficient mice for TLR 2/4 in the same model (Rusai et al 2010). Moreover, the blocking of IL-1 RA was able to ameliorate kidney injury in a rat model of I/R (Rusai et al 2008).…”
Section: The Role Of Inflammation and Fibrosis In Chronic Kidney Diseasesupporting
confidence: 54%
“…HMGB1 can, however, also induce activation of intracellular signaling pathways via interaction with PRRs other than RAGE including: Toll-like receptor (TLR) 2, TLR-4 and inflammasome NACHT, LRR and PYD domains-containing protein 3 (Nlrp3) [32,33] . We and others have shown that ␣ HMGB1-treated WT mice, TLR2 KO, TLR4 KO and Nlrp3 KO mice display a similar phenotype following renal I/R [16,17,21,30,31,[34][35][36] . Together, these reports implicate that the deleterious effect of HMGB1 in the development of renal I/R injury is not mediated by RAGE signaling, but rather by TLRs and/or Nlrp3.…”
Section: Discussionmentioning
confidence: 71%
“…Many PRRs, including TLRs, are expressed in renal epithelial cells (46)(47)(48)(49)(50)(51)(52)(53)(54). The precise distribution of tubular TLRs remains somewhat uncertain.…”
Section: How the Innate Immune System Senses Trouble And Causes Troubmentioning
confidence: 99%